The native shrub, Piliostigma reticulatum, as an ecological “resource island” for mango trees in the Sahel - Hernández, R.R.; Debenport, S.J.; Leewis, M.C.C.; Ndoye, F.; Soumare, A.; Thuita, Moses N.; Gueye, M.; Miambi, E.; Chapuis-Lardy, L.; Diedhiou, I.; Dick, R.P. (Elsevier, 2015)
African farmers are increasingly adopting sustainable agricultural practices including use of native shrub intercropping approaches. In one village of Sénégal (near Thiès) it was reported that farmers planted mango (Mangifera indica) seedlings within the canopies of a native shrub (Piliostigma reticulatum). Anecdotal information and qualitative observations suggested that the presence of P. reticulatum promoted soil quality and a competitive advantage for establishing mango plantations. We hypothesized that soil chemical and microbial properties of mango rhizosphere soil growing in the presence of P. reticulatum would be significantly improved over soils associated with mango growing outside the influence of P. reticulatum. The results showed that mango-shrub interplanting significantly lowered pH, and increased arbuscular mycorrhizal fungi (AMF) colonization of mango roots, enzyme activities, and microbial biomass compared to mango alone. Phylogenetic analyses by PCR-denaturing gradient gel electrophoresis (DGGE) showed that community structures of fungi, bacteria, and bacterial genes responsible for denitrification (nirK) of the soil from the rooting zone of the mango-shrub intercropping system were distinct from all other soil outside the influence of P. reticulatum. It is concluded that P. reticulatum enhances soil biological functioning and that there is a synergistic effect of intercropping mango with the native shrub, P. reticulatum, in soil quality with a more diverse community, greater AMF infection rates, and greater potential to perform decomposition and mineralize nutrients.African farmers are increasingly adopting sustainable agricultural practices including use of native shrub intercropping approaches. In one village of Sénégal (near Thiès) it was reported that farmers planted mango (Mangifera indica) seedlings within the canopies of a native shrub (Piliostigma reticulatum). Anecdotal information and qualitative observations suggested that the presence of P. reticulatum promoted soil quality and a competitive advantage for establishing mango plantations. We hypothesized that soil chemical and microbial properties of mango rhizosphere soil growing in the presence of P. reticulatum would be significantly improved over soils associated with mango growing outside the influence of P. reticulatum. The results showed that mango-shrub interplanting significantly lowered pH, and increased arbuscular mycorrhizal fungi (AMF) colonization of mango roots, enzyme activities, and microbial biomass compared to mango alone. Phylogenetic analyses by PCR-denaturing gradient gel electrophoresis (DGGE) showed that community structures of fungi, bacteria, and bacterial genes responsible for denitrification (nirK) of the soil from the rooting zone of the mango-shrub intercropping system were distinct from all other soil outside the influence of P. reticulatum. It is concluded that P. reticulatum enhances soil biological functioning and that there is a synergistic effect of intercropping mango with the native shrub, P. reticulatum, in soil quality with a more diverse community, greater AMF infection rates, and greater potential to perform decomposition and mineralize nutrients.African farmers are increasingly adopting sustainable agricultural practices including use of native shrub intercropping approaches. In one village of Sénégal (near Thiès) it was reported that farmers planted mango (Mangifera indica) seedlings within the canopies of a native shrub (Piliostigma reticulatum). Anecdotal information and qualitative observations suggested that the presence of P. reticulatum promoted soil quality and a competitive advantage for establishing mango plantations. We hypothesized that soil chemical and microbial properties of mango rhizosphere soil growing in the presence of P. reticulatum would be significantly improved over soils associated with mango growing outside the influence of P. reticulatum. The results showed that mango-shrub interplanting significantly lowered pH, and increased arbuscular mycorrhizal fungi (AMF) colonization of mango roots, enzyme activities, and microbial biomass compared to mango alone. Phylogenetic analyses by PCR-denaturing gradient gel electrophoresis (DGGE) showed that community structures of fungi, bacteria, and bacterial genes responsible for denitrification (nirK) of the soil from the rooting zone of the mango-shrub intercropping system were distinct from all other soil outside the influence of P. reticulatum. It is concluded that P. reticulatum enhances soil biological functioning and that there is a synergistic effect of intercropping mango with the native shrub, P. reticulatum, in soil quality with a more diverse community, greater AMF infection rates, and greater potential to perform decomposition and mineralize nutrients.African farmers are increasingly adopting sustainable agricultural practices including use of native shrub intercropping approaches. In one village of Sénégal (near Thiès) it was reported that farmers planted mango (Mangifera indica) seedlings within the canopies of a native shrub (Piliostigma reticulatum). Anecdotal information and qualitative observations suggested that the presence of P. reticulatum promoted soil quality and a competitive advantage for establishing mango plantations. We hypothesized that soil chemical and microbial properties of mango rhizosphere soil growing in the presence of P. reticulatum would be significantly improved over soils associated with mango growing outside the influence of P. reticulatum. The results showed that mango-shrub interplanting significantly lowered pH, and increased arbuscular mycorrhizal fungi (AMF) colonization of mango roots, enzyme activities, and microbial biomass compared to mango alone. Phylogenetic analyses by PCR-denaturing gradient gel electrophoresis (DGGE) showed that community structures of fungi, bacteria, and bacterial genes responsible for denitrification (nirK) of the soil from the rooting zone of the mango-shrub intercropping system were distinct from all other soil outside the influence of P. reticulatum. It is concluded that P. reticulatum enhances soil biological functioning and that there is a synergistic effect of intercropping mango with the native shrub, P. reticulatum, in soil quality with a more diverse community, greater AMF infection rates, and greater potential to perform decomposition and mineralize nutrients.